2017
DOI: 10.1111/vru.12528
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of interthalamic adhesion size as an indicator of brain atrophy in dogs with and without cognitive dysfunction

Abstract: Interthalamic adhesion thickness has been previously described as a parameter for quantifying canine brain atrophy and hypothesized to correlate with brain height or ventricular size. However, studies testing this hypothesis are lacking. This retrospective cross-sectional study aimed to compare interthalamic adhesion thickness, interthalamic adhesion thickness/brain height ratio, and interthalamic adhesion thickness/brain height ratio/lateral ventricle to brain height ratio values in dogs with and without cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…The apparent absence of cognitive dysfunction in the group of dogs with nearly twice the number of microhemorrhages as in the dogs with cognitive dysfunction suggests that factors other than microhemorrhages might be responsible for cognitive dysfunction. Our results support the observations of previous investigators, who also found smaller interthalamic adhesions in dogs with cognitive dysfunction than in control dogs (Hasegawa et al, 2005;Noh et al, 2017). However, decreases in interthalamic adhesion size are not specific for cognitive dysfunction and have been reported sporadically in other disorders that can cause brain atrophy (Hasegawa et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The apparent absence of cognitive dysfunction in the group of dogs with nearly twice the number of microhemorrhages as in the dogs with cognitive dysfunction suggests that factors other than microhemorrhages might be responsible for cognitive dysfunction. Our results support the observations of previous investigators, who also found smaller interthalamic adhesions in dogs with cognitive dysfunction than in control dogs (Hasegawa et al, 2005;Noh et al, 2017). However, decreases in interthalamic adhesion size are not specific for cognitive dysfunction and have been reported sporadically in other disorders that can cause brain atrophy (Hasegawa et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Dogs with cognitive dysfunction have smaller interthalamic adhesion heights than similarly aged control dogs without cognitive dysfunction (Hasegawa et al, 2005;Noh et al, 2017). This change is not considered specific for CCD but is indicative of a generalized neurodegenerative process (Hasegawa et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…However, the ratio did reveal a significant increase in relative lateral ventricle height with increased age. This could be due to reduction in brain volume with age a phenomenon previously reported in dogs …”
Section: Discussionmentioning
confidence: 60%
“…The method of measurement of lateral ventricle height and brain height used were subtly altered from the method used in dogs, as MRI enabled accurate assessment of both values in a single plane, however, relatively limited soft tissue detail necessitated choosing the greatest height of the lateral ventricle for measurement rather than a simple midline height. Additionally, bony rather than soft tissue landmarks were chosen for brain height to increase reliability of measurement on CT . The repeatability of the measure was confirmed by excellent interobserver reliability testing.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that interthalamic adhesion thickness, interthalamic adhesion thickness/brain height ratio, and lateral ventricle to brain height ratio were all significantly lower in dogs with signs of cognitive dysfunction than in dogs with no cognitive function. These metrics were validated for use in quantifying brain atrophy in patients (42). Like AD, CCD cannot be cured.…”
Section: Canine Cognitive Dysfunctionmentioning
confidence: 99%